Radiography lecturers' understanding of a socially responsive curriculum. Issue 3 (August 2022) - Hudson, L.; Engel-Hills, P.; Davidson, F.; Naidoo, K.
Abstract: Introduction: In health professions education (HPE), focus is placed on developing clinically competent practitioners who can function within their professional scope in a broad range of health care contexts. In this study, the authors investigated diagnostic radiography lecturers' understanding of how students become socially responsive. The concept of 'critical consciousness' was explored as an intervention of being a transformer in the local environment. This places focus on learning and teaching that aims to develop radiography graduates who are critically conscious, such that they can take up the challenges of healthcare in their environment, in addition to being clinically competent in their field. The study under discussion therefore sought to find out how radiography lecturers understand a socially responsive curriculum at a University of Technology in the South African context. Method: A qualitative, exploratory design was used where curriculum documents were reviewed and from which stimulus points were identified for a semi-structured focus group interview with radiography lecturers followed by five individual interviews. All interviews were audio-recorded, transcribed, coded and analysed through a process of thematic analysis. Results: Four dominant themes emerged from the analysis, namely i) diverse understandings of critical consciousness, ii) becoming a reflective practitioner, iii) a need for curriculum transformation and iv) emerging pedagogies. Conclusion: Critical reflection by both the radiography students and lecturers is key to developing social awareness and critical consciousness which could drive critical motivation and critical action to effect social change. It is recommended that the current curriculum should be reviewed and transformed to include constructive reflective practice. Implications for practice: Dedicated time should be scheduled, in the curriculum, to allow students and lecturers to engage in meaningful constructive reflection to enhance socially responsive practice.